Pemaknaan Anggota the Jakmania Mengenai Indonesia Batal Menjadi Tuan Rumah Piala Dunia U20 dalam Talkshow Rosi - ‎Kevin, Kevin; Agustrijanto, Agustrijanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
Indonesia's failure to host the U20 World Cup was conveyed by players from the Indonesian U20 National Team following Rosi's YouTube video content on Kompas TV. The aim of this research is to find out the meaning of members of The Jakmania regarding Indonesia's cancellation of hosting the U20 World Cup in Indonesia in Rosi's talk show. The research method used in the research is the audience reception analysis method. The theory used in this research is Stuart Hall's Encoding-Decoding Theory. This research approach uses qualitative descriptive qualitative research. The results of the research showed that five informants were in the Dominant Hegemony position regarding the discussion of Indonesia's failure to host the U20 World Cup, one informant was in the Negotiation position regarding the discussion of Indonesia's future opportunities to host the World Cup and three informants were in the Opposition position regarding the discussion of the impact of PSSI after failed to host the U20 World Cup.